The information content of physiological and epileptic brain activity. (24th January 2013) - Trevelyan, Andrew J.; Bruns, Willy; Mann, Edward O.; Crepel, Valerie; Scanziani, Massimo
Abstract : Abstract Cerebral cortex is a highly sophisticated computing machine, feeding on information provided by the senses, which is integrated with other, internally generated patterns of neural activity, to trigger behavioural outputs. Bit by bit, we are coming to understand how this may occur, but still, the nature of the 'cortical code' remains one of the greatest challenges in science. As with other great scientific challenges of the past, fresh insights have come from a coalescence of different experimental and theoretical approaches. These theoretical considerations are typically reserved for cortical function rather than cortical pathology. This approach, though, may also shed light on cortical dysfunction. The particular focus of this review is epilepsy; we will argue that the information capacity of different brain states provides a means of understanding, and even assessing, the impact and locality of the epileptic pathology. Epileptic discharges, on account of their all‐consuming and stereotyped nature, represent instances where the information capacity of the network is massively compromised. These intense discharges also prevent normal processing in surrounding territories, but in a different way, through enhanced inhibition in these territories. Information processing is further compromised during the period of post‐ictal suppression, during interictal bursts, and also at other times, through more subtle changes in synaptic function. We also comment on information processing in other more physiological brain states.